Dampak Pembiayaan Kredit Perbankan terhadap Nilai Tambah Industri Pengolahan di Indonesia (Jurnal Kebijakan Ekonomi, 2014)
This study aims to measure the effect of bank credit financing to value-added of manufacturing industry in Indonesia. This study uses the data of manufacturing industry sub-sector level. The data used are sub-sector credit, value added, labor, fixed capital, the minimum wage, the exchange rate, and the Gross Domestic Produc. This study period is 2002 – 2012 and using a Two-Stage Least Square with Fixed Effect as a estimation methode. Finally, the results showed that the significant effect of bank credit financing to encourage value-added manufacturing industry in Indonesia.